Green Accounting Education and Digital Innovation: The Role of Accounting Education Students in Achieving The SDGs - Satiti, Wening Tansah; Narayani, Putri Restu; Ivada, Elvia (Universitas Muhammadiyah Surakarta, 2025)
The accelerating environmental crisis, marked by record-high greenhouse gas emissions and persistent ecological degradation, demands transformative action across sectors. Education, particularly in accounting, holds a strategic role in bridging economic practices with ecological responsibility. This conceptual paper presents perspective of the integration of green accounting education and digital innovation as a pathway to support the Sustainable Development Goals (SDGs). It highlights the role of Accounting Education students as future educators and change agents who can cultivate sustainability values through interactive e-modules and short educational videos. By embedding green accounting into curricula and leveraging digital tools, students are positioned to enhance environmental awareness, critical thinking, and pro-environmental behavior. The study underscores that awareness must be followed by concrete action, where every step from creating educational content to practicing environmentally responsible accounting contributes to a collective transformation toward a sustainable future.